2021
DOI: 10.3390/ijerph182312420
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Using the Surgical Mask and FFP2 during the 6-Min Walking Test. A Randomized Controlled Trial

Abstract: During the COVID-19 pandemic, the use of masks has been recommended as a containment measure. The mask is a hindrance to normal breathing that causes discomfort. This could put more work on the respiratory accessory muscles, and, consequently, these muscles could see their tone increase. For this reason, during this clinical trial (registered in clincaltrials.gov, number: NCT04789603), it was observed whether the use of the mask produced changes in the distance traveled, in the heart rate, in the oxygenometry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 31 publications
1
34
0
2
Order By: Relevance
“…In our study, in which we performed the 6MWT in the same patient with and without a mask, we observed a shorter distance walked, lower blood oxygen, higher systolic BP, and a greater subjective perception of dyspnea in mask wearers at the end of the test. Other studies conducted in healthy volunteers, such as the study by Cabanillas et al, 10 and Person et al, 11 found no differences in 6MWT parameters, whereas the study conducted by Kyung et al 12 that included 97 COPD patients showed similar results to ours.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…In our study, in which we performed the 6MWT in the same patient with and without a mask, we observed a shorter distance walked, lower blood oxygen, higher systolic BP, and a greater subjective perception of dyspnea in mask wearers at the end of the test. Other studies conducted in healthy volunteers, such as the study by Cabanillas et al, 10 and Person et al, 11 found no differences in 6MWT parameters, whereas the study conducted by Kyung et al 12 that included 97 COPD patients showed similar results to ours.…”
supporting
confidence: 86%
“…We assessed the subjective feeling of dyspnea in our study by using the modified Borg scale 17 , 18 : significant differences were found between the pre- and post-test values. Person et al 11 and Cabanillas et al, 10 using a visual analogue scale (VAS), found a significant increase in dyspnea in the test performed with the mask (1 cm on VAS). 17 …”
mentioning
confidence: 97%
“…Most included studies were randomized crossover studies ( n = 42), while two studies were randomized controlled trials [ 24 , 25 ] and one study used a non-randomized repeated measure [ 26 ]. Except for three studies that involved children [ 27 – 29 ], all the other studies involved adults, including athletes ( n = 3) [ 30 – 32 ], recreational athletes ( n = 2) [ 33 , 34 ], and healthy adults ( n = 37) [ 3 , 12 – 15 , 18 , 24 – 26 , 35 – 62 ], with a total of 1264 participants (708 men, 556 women) included.…”
Section: Resultsmentioning
confidence: 99%
“…The face masks increased airflow resistance, facial skin temperature and moisture or heat of the inhaled air, resulting in increased dyspnea [ 26 , 27 , 28 ]. Previous studies reported that healthy subjects wearing face masks recorded similar distances walked during the 6MWT compared to no mask [ 17 , 25 , 29 ], while changes after the 6MWT were found in heart failure or chronic lung disease patients [ 30 , 31 ]. This study involved no participants with heart failure or chronic lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects were randomly assigned to six conditions with forty subjects per condition, including: (1) sitting quietly wearing no mask for 10 min, (2) sitting quietly wearing a cloth mask for 10 min, (3) sitting quietly wearing a surgical mask for 10 min, (4) performing a 6MWT with no mask, (5) performing a 6MWT wearing a cloth mask and (6) performing a 6MWT wearing a surgical mask. The sample size was calculated using a power of 0.8, power analysis with an effect size f of 0.20 and alpha of 0.05 [ 17 ]. Inclusion and exclusion criteria were as follows: aged 65 or older with normal body mass index (BMI = 18.5–24.9 kg/m 2 ) [ 18 ] and can perform a 6MWT, no previous problems of unstable cardiorespiratory diseases, neurological diseases with imbalance problems, musculoskeletal disease affecting standing or walking and arterial hypertension with the possibility of left ventricular dysfunction was measured using an echocardiogram.…”
Section: Methodsmentioning
confidence: 99%